2018
DOI: 10.1002/jbio.201700302
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of modeling liver thermal damage using minimally invasive optical method adequate for in situ measurement

Abstract: Liver thermal ablation techniques have been widely used for the treatment of liver cancer. Kinetic model of damage propagation play an important role for ablation prediction and real-time efficacy assessment. However, practical methods for modeling liver thermal damage are rare. A minimally invasive optical method especially adequate for in situ liver thermal damage modeling is introduced in this paper. Porcine liver tissue was heated by water bath under different temperatures. During thermal treatment, diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“… αt=()1goodbreak−αnAeEitalicRT, where, A is the frequency factor (1/s), and Δ E is the activation energy for the irreversible damage reaction (J/mol). The parameters A and Δ E are dependent on the type of tissue and have been characterized for liver tissues to be A = 7.39 × 10 39 s −1 and Δ E = 2.577 · 10 5 J/mol 15 …”
Section: Thermal and Electrical Properties Of The Tissuementioning
confidence: 99%
See 1 more Smart Citation
“… αt=()1goodbreak−αnAeEitalicRT, where, A is the frequency factor (1/s), and Δ E is the activation energy for the irreversible damage reaction (J/mol). The parameters A and Δ E are dependent on the type of tissue and have been characterized for liver tissues to be A = 7.39 × 10 39 s −1 and Δ E = 2.577 · 10 5 J/mol 15 …”
Section: Thermal and Electrical Properties Of The Tissuementioning
confidence: 99%
“…Since at room temperature, the maximum value of permittivity is 55 for tumor tissue, therefore, the maximum value of permittivity in the level is 55. Further, the output parameters are ablation diameter (T and A) obtained from simulated results in Comsol Multiphysics and only 27 combinations were required to analyze the result using the Taguchi method, as shown in Table 6 15 . Also, since the the ablation diameter in Table 6 is obtained by considering temperature independent tissue thermo‐electrical paramaters therefore, a reduction of 4 and 2 mm along axial and transversal diameter, respectively have been incorporated as discussed in Section 3.…”
Section: Ablation Diameter Predictionmentioning
confidence: 99%
“…The temperature-dependent heat properties and Arrhenius kinetics accurately predict the timedependent ablation zone. 30 Taguchi's statistical method is used to accurately predict the weightage of each biological, thermal, and electromagnetic property in determining the ablation diameter. Taguchi method is adopted because it is robust, requires lesser time, and lesser number of experiments as compared to the conventional factorial method.…”
Section: Introductionmentioning
confidence: 99%
“…A 3‐D finite element model (FEM) consisting of thermophysical heat property along with Penne's bioheat model and Arrhenius kinetics is used to simulate the ablation environment. The temperature‐dependent heat properties and Arrhenius kinetics accurately predict the time‐dependent ablation zone 30 . Taguchi's statistical method is used to accurately predict the weightage of each biological, thermal, and electromagnetic property in determining the ablation diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Liver cancer is the rst cancer type to be used by MWA, and it has gradually become one of the reliable methods to treat and cure liver cancer since the 1990s 12 . Studies have shown that the thermal damage of liver tissue under MWA is a dynamic process related to temperature and time 13,14 . Some researchers have con rmed that thermal injury signi cantly affects the optical properties of liver tissue 15,16 .…”
Section: Introductionmentioning
confidence: 99%